Female social and sexual interest across the menstrual cycle: the roles of pain, sleep and hormones - Gray Peter B; Manlove Heidi A; Guillermo Chrisalbeth J; Zava David T; Marrs Chandler R (BMC, 2010)
Abstract Background Although research suggests that socio-sexual behavior changes in conjunction with the menstrual cycle, several potential factors are rarely taken into consideration. We investigated the role of changing hormone concentrations on self-reported physical discomfort, sleep, exercise and socio-sexual interest in young, healthy women. Methods Salivary hormones (dehydroepiandrosterone sulfate-DHEAS, progesterone, cortisol, testosterone, estradiol and estriol) and socio-sexual variables were measured in 20 women taking oral contraceptives (OC group) and 20 not using OCs (control group). Outcome measures were adapted from questionnaires of menstrual cycle-related symptoms, physical activity, and interpersonal relations. Testing occurred during menstruation (T1), mid-cycle (T2), and during the luteal phase (T3). Changes in behavior were assessed across time points and between groups. Additionally, correlations between hormones and socio-behavioral characteristics were determined. Results Physical discomfort and sleep disturbances peaked at T1 for both groups. Exercise levels and overall socio-sexual interest did not change across the menstrual cycle for both groups combined. However, slight mid-cycle increases in general and physical attraction were noted among the control group, whereas the OC group experienced significantly greater socio-sexual interest across all phases compared to the control group. Associations with hormones differed by group and cycle phase. The estrogens were correlated with socio-sexual and physical variables at T1 and T3 in the control group; whereas progesterone, cortisol, and DHEAS were more closely associated with these variables in the OC group across test times. The direction of influence further varies by behavior, group, and time point. Among naturally cycling women, higher concentrations of estradiol and estriol are associated with lower attraction scores at T1 but higher scores at T3. Among OC users, DHEAS and progesterone exhibit opposing relationships with attraction scores at T1 and invert at T3. Conclusions Data from this study show no change across the cycle in socio-sexual interest among healthy, reproductive age women but higher social and physical attraction among OC users. Furthermore, a broader range of hormones may be associated with attraction than previously thought. Such relationships differ by use of oral contraceptives, and may either reflect endogenous hormone modulation by OCs and/or self-selection of sexually active women to practice contraceptive techniques.